Translation of heteroglossia :|the case of Turkish translations of heteroglot novels by black British women writers - İdin, Fatma. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2010., 2010)
The aim of the present study is to explore how heteroglossia is treated in Turkish translations of novels. Mikhail Bakhtin’s theoretical views on heteroglossia are employed in order to carry out stylistic analyses of novels by five Black British women writers: Brick Lane by Monica Ali, Small Island by Andrea Levy, The Ventriloquist’s Tale by Pauline Melville, Trumpet by Jackie Kay and White Teeth by Zadie Smith. After a discussion of the discourse on heteroglossia within the scope of Translation Studies, the Turkish translations of the novels, which are Brick Lane (2004), Küçük Ada (2006), Karnından Konusanın Öyküsü (2000), Trompet (2000) and Đnci Gibi Disler (2001) are analyzed within a descriptive and target-oriented framework. It is observed that different strategies are used by the individual translators and that choices have been made in an inconsistent way. Specifically, the translators tend to adopt hybrid translation and oscillate between the strategies of domestication and foreignization. It is argued that, however challenging it is to translate heteroglossia, it is still possible to foreground traces of the linguistic and cultural specificity of heteroglot novels. On the basis of the findings of this study with respect to the target context, it is concluded that these texts and their translations are likely to make the reader aware of the diversity of voices. Furthermore, it is emphasized that these translations tend to destabilize the expectation of fluent translations and contribute to the achivement of cultural identity through heteroglossia.
Keywords: Comic strip characters.; Comic books, strips, etc.